(untitled) (American Journal of Islam and Society, 2006)
Most classical-era Qur’anic studies scholars, among then Abu `Ubayd al-Qasim ibn Sallam (d. 224 AH), Makki ibn Abi Talib (d. 437 AH), Abd al-Rahman ibn al-Jawzi (d. 597 AH), Badr al-Din al- Zarkashi (d. 794 AH), and Jalal al-Din al-Suyuti (d. 911 AH) were enthusiastic supporters of the theory of abrogation. They claimed that the Qur’an contains three types of abrogation1: suspension of certain verses’ practical dimension only, expurgation of both the verses and their rulings, and exclusion of the verses even though their rulings are still valid. To substantiate their approach, they advanced hadiths comprising statements supposedly made by both the Companions (Sahabah) and the Followers (Tabi`un). A rational and critical scrutiny of these hadiths will reveal whether they can form the basis of such arguments. I will check the nature of these hadiths’ chains of narrators and weigh the views attributed to early Muslim scholars against reason. As regards the first category, several of my articles on these arguments have been published elsewhere.2 This article, which examines the remaining two categories, consists of two dimensions: applying the hadith criticism principle to these hadiths and checking their information in a rational manner.